Perturbation solutions for magnetohydrodynamics (MHD) flow of in a non-newtonian fluid between concentric cylinders - Yürüsoy, Muhammet; Güler, Ömer Faruk (Zielona Góra: Uniwersytet Zielonogórski)
The steady-state magnetohydrodynamics (MHD) flow of a third-grade fluid with a variable viscosity parameter between concentric cylinders (annular pipe) with heat transfer is examined. The temperature of annular pipes is assumed to be higher than the temperature of the fluid.
Keywords: MHD flow; perturbation technique; annular flow; third grade fluid